ESTETIKA PARADOKS WAYANG PUNAKAWAN DALAM TELAAH TAFSIR SIMBOLIK SEBAGAI SUMBER PENDIDIKAN KARAKTER - Slamet Subiyantoro; Mohamad Suharto; Dimas Fahrudin (Jurnal Pendidikan Karakter, 2022)
This research is based on the problem of wayang purwa which is currently starting to not get the attention of the public, especially the younger generation. This study aims to explore the paradoxical aesthetics of the Punakawan wayang through symbolic interpretation. This study uses a qualitative approach with the Punakawan puppet as the object and Dhalang as the research subject. Sources of research data in the form of informants, places events, as well as documents or archives. Data were collected using in-depth interviews, participatory observation, and document analysis. The validity of the data was tested by means of triangulation of sources and review of informants. Data were analyzed using an interactive model with data reduction, data display, and verification procedures. The results showed that the outer structure of the wayang punokawan has distinctive features and characteristics. The inner structure is more about meanings and values that are integrated with the outer structure. In the study of semiotics, wayang punokawan represents or is interpreted based on the values and meanings contained (internal structure). The paradoxical aesthetic value of the opposite between the outer and inner structures of wayang punokawan in Javanese culture is essentially learning the noble values of humanity to be applied in school learning, lectures, and community life.